Faktor-Faktor yang Berhubungan dengan Ketidaklengkapan Imunisasi Dasar Pada Anak Umur < 5 Tahun di Kotamadya Viqueque, Timor Leste - Pinto, João Menezes; Sutiningsih, Dwi; Adi, Mateus Sakundarno; Muh, Fauzi; Martini, Martini (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2025)
Background: Immunization is an effective way to prevent infectious diseases in children through vaccination, there are still some children aged <5 years in Viqueque Municipality who have not received complete basic immunization, the purpose of this study is to determine the determinants of incomplete basic immunization in children aged <5 years in Viqueque Municipality, Timor Leste.Methods: Observational analysis was used in this study with cross-sectional design. All parents/caregivers of children <5 years were the research subjects, the sample was obtained by accidental sampling technique, the independent variables were education, knowledge, distance to health facilities, place of born, parenting and ownership of LISIO, the dependent variable was incomplete basic immunization, data collection through interviews from the results of validity and reliability test of the questionnaire. Analysis using Chi-square test and multiple logistic regression.Results: The results showed that the variables of knowledge (p-value 0.001), distance to health facilities (p-value 0.027), place of birth (p-value 0.000) and ownership of LISIO (p-value 0.004) were associated with incomplete primary immunisation. The most influential variable was place of birth (OR=6.52, 95%CI:3.23-13.17), followed by knowledge (OR=2.91, 95%CI:1.50-5.61) and distance to health facilities (OR=2.74, 95%CI:1.22-6.14).Conclusion: The variables of place of birth in non-health facilities, distance from health facilities and low knowledge affect the incompleteness of basic immunisation of children, the importance of health education and promotion by health professionals in the community to give birth in health facilities and community participation in all health service programmes in the community.